Replication Errors Made During Oogenesis Lead to Detectable De Novo mtDNA Mutations in Zebrafish Oocytes with a Low mtDNA Copy Number. Issue 4 (1st December 2016) - Otten, Auke B C; Stassen, Alphons P M; Adriaens, Michiel; Gerards, Mike; Dohmen, Richard G J; Timmer, Adriana J; Vanherle, Sabina J V; Kamps, Rick; Boesten, Iris B W; Vanoevelen, Jo M; Muller, Marc; Smeets, Hubert J M
Abstract: Of all pathogenic mitochondrial DNA (mtDNA) mutations in humans, ∼25% is de novo, although the occurrence in oocytes has never been directly assessed. We used next-generation sequencing to detect point mutations directly in the mtDNA of 3–15 individual mature oocytes and three somatic tissues from eight zebrafish females. Various statistical and biological filters allowed reliable detection of de novo variants with heteroplasmy ≥1.5%. In total, we detected 38 de novo base substitutions, but no insertions or deletions. These 38 de novo mutations were present in 19 of 103 mature oocytes, indicating that ∼20% of the mature oocytes carry at least one de novo mutation with heteroplasmy ≥1.5%. This frequency of de novo mutations is close to that deducted from the reported error rate of polymerase gamma, the mitochondrial replication enzyme, implying that mtDNA replication errors made during oogenesis are a likely explanation. Substantial variation in the mutation prevalence among mature oocytes can be explained by the highly variable mtDNA copy number, since we previously reported that ∼20% of the primordial germ cells have a mtDNA copy number of ≤73 and would lead to detectable mutation loads. In conclusion, replication errors made during oogenesis are an important source of de novo mtDNA base substitutions and their location and heteroplasmy level determine their significance.